Burkitt's lymphoma of the duodenum in a patient with AIDS - Corti,Marcelo (2007)
Non-Hodgkin's lymphoma of B-cell type is the second most common neoplasm after Kaposi's sarcoma, among patients with human immunodeficiency virus infection. Most non-Hodgkin's lymphoma cases that are associated with acquired immunodeficiency syndrome involve extranodal sites, especially the digestive tract and the central nervous system. We report a case of primary lymphoma of the duodenum in a patient with AIDS. Upper gastrointestinal endoscopy revealed pseudopolypoid masses found in the second portion of the duodenum. A complete diagnostic study including histological, immunohistochemical and virological analyses showed high-grade B-cell Burkitt's lymphoma. The Epstein-Barr virus genome was detected in biopsies by immunohistochemical and in situ hybridization.